Evaluasi Kompleksitas Pendekodean MAP pada Kode BCH Berdasarkan Trellis Terbagi - Emir Husni; Dimas Pamungkas (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
Soft decoding of block codes can be done by representing the block code into the trellis. One method of soft decoding commonly used is the maximum a posteriori probability (MAP). However, the implementation of this method requires a high computational complexity. Reducing the complexity can be done by changing the trellis shape of the block code. This paper shows the process of the block code’s trellis formation and the evaluation of computational complexity and bit error ratio for every trellis shape of block codes. The evaluation of codes using the MAP method is compared to the evaluation of the soft output Viterbi algorithm (SOVA) method. The result shows that soft decoding using MAP method is better than soft coding using SOVA method and hard decoding method.